Influence of DND on retailoring and hardening of details of fuel facilities components. - Скобло, Т.С.; Клочко, О.Ю.; Сидашенко, А.И.; Плугарев, А.В.; Олейник, А.И. (Problems of Tribology, 2015)
Skoblo T.S., Klochko O.Yu., Sidashenko A.I., Plugataryov A.V. Oleynik A.K. Influence of DND on retailoring and hardening of details of fuel facilities components. Facilities development and technologies of DND modification with feeding; their influence on structure and properties of bichromated coating allowing to retailor and harden the fuel facilities components in foreign vehicles in conditions approachable within repair stations.